Does transpersonal trust moderate the association between chronic conditions and general practitioner visits in the oldest old? Results of the AgeCoDe and AgeQualiDe study. Issue 8 (24th June 2019) - Hajek, André; Brettschneider, Christian; Eisele, Marion; Lühmann, Dagmar; Mamone, Silke; Wiese, Birgitt; Weyerer, Siegfried; Werle, Jochen; Fuchs, Angela; Pentzek, Michael; Stein, Janine; Luck, Tobias; et al.
Abstract : Aim: The purpose of this study was to investigate whether transpersonal trust (TPT) moderates the relationship between chronic conditions and general practitioner (GP) visits among the oldest old in Germany. Methods: The multicenter prospective cohort Study on Needs, health service use, costs and health‐related quality of life in a large sample of oldest old primary care patients (85+) (AgeQualiDe) was carried out. Individuals were recruited through GP offices at six study centers in Germany (follow‐up wave 7). Primary care patients were aged ≥85 years ( n = 861, mean age 89.0 years; range 85–100 years). The self‐reported number of outpatient visits to the GP was used as the outcome measure. To explore religious and spiritual beliefs, the short form of the Transpersonal Trust scale was used. The presence or absence of 36 chronic conditions was recorded by the GP. Results: Multiple Poisson regressions showed that GP visits were positively associated with the number of chronic conditions (incidence rate ratio 1.03, P < 0.05). TPT moderated the relationship between chronic conditions and GP visits (incidence rate ratio 1.01, P < 0.05). The association between chronic conditions and GP visits was significantly more pronounced when TPT was high. Conclusion: Our findings highlight the importance of TPT in the relationship between chronic conditions and GP visits. Future longitudinal studies are required to clarify this subject further.Geriatr Gerontol Int 2019; 19: 705–710 .